Attempted Suicide by Massive Warfarin Ingestion Conservatively Managed Using Phytonadione - March, Katherine L.; Patel, Kruti S.; Twilla, Jennifer D. (Case Reports in Hematology, 2016)
Treatment strategies for acute toxicity following massive ingestion of warfarin are not well described in the literature. Warfarin is the primary oral anticoagulation agent used in the treatment of thromboembolic disease, and patients with acute toxicity are at risk for life-threatening hemorrhages. Treatment options include phytonadione (vitamin K1), fresh frozen plasma (FFP), and prothrombin complex concentrates (PCCs) used alone or in combination. FFP and PCC can be associated with volume complications, undesirable thromboembolic events, and increased costs. We describe the case of a 63-year-old female with acute warfarin toxicity following a massive ingestion of warfarin (420 mg–450 mg) in an attempt to commit suicide. Upon arrival to the emergency department, serial INR checks were initiated to help guide dosing strategy and later adjusted based on INR response to treatment using only phytonadione.